2009
DOI: 10.2337/dc08-1200
|View full text |Cite
|
Sign up to set email alerts
|

Will People With Type 2 Diabetes Speak to Family Members About Health Risk?

Abstract: OBJECTIVE—This study aimed to assess the potential for communication of familial risk by patients with type 2 diabetes. RESEARCH DESIGN AND METHODS—A questionnaire was completed by a random sample of patients with type 2 diabetes registered with a hospital diabetes clinic. RESULTS—Two-thirds of patients (65%) had spoken to at least one sibling or child about diabetes risk. They were more likely to believe their family was at risk, to worry about their family developing diabetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 13 publications
6
44
0
Order By: Relevance
“…As reported elsewhere[18], three quarters of patients with type 2 diabetes were willing to take on this health-promoting role within families. This study indicates that relatives of patients with type 2 diabetes are also supportive of being informed by their relatives of their risk and of strategies to help reduce this risk.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As reported elsewhere[18], three quarters of patients with type 2 diabetes were willing to take on this health-promoting role within families. This study indicates that relatives of patients with type 2 diabetes are also supportive of being informed by their relatives of their risk and of strategies to help reduce this risk.…”
Section: Discussionmentioning
confidence: 75%
“…In this study we used patients with type 2 diabetes involved in an associated study[18] as the basis for sampling. This patient population was a random sample of patients with type 2 diabetes (n = 607 eligible patients) registered with a hospital diabetes clinic (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The studies demonstrated that professional and comprehensive education of families and caregivers who support diabetes patients at home is a measure preventing the risk of errors in patient care [49] and promoting better implementation of medical recommendations [50]. The education of patient families helps to improve their competences, effective care and nursing and involvement in the basic and secondary prevention of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the information need is low due to underestimation of the seriousness of the condition [33] or limited awareness about the role of genetics and shared environment in the aetiology [34,35]. Recent trends indicating a growing awareness of family risk and worry about the development of T2DM in offspring [36,37] is not yet reflected in our results. Possibly, people found genetic information about T2DM, GDM or MODY/MIDD/LADA subtypes on other websites than the one we studied.…”
Section: Discussionmentioning
confidence: 90%